HIPERREALITAS KONSUMSI TANDA DAN MAKNA PADA TRENDING FASHION JILBAB OLEH MAHASISWI - Fifi Rachmawati Alfi'ah; Abdul Rahman; Okta Hadi Nurcahyono (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2020)
The study objective is to examine the excessive consumption of jilbab fashion trends by university students. This research is a descriptive study with qualitative methods and determined informants using purposive sampling. The researchers use primary and secondary both data all were collected through interviews, observation, and documentation. After the data were triangulated by sources and methods then we analyzed data using the simulakra theory of Jean P. Baudrillard to see the excessive consumption of jilbab fashion trends by students. The main results indicate that the growing jilbab fashion trends through social media have made student’s experience enjoy excessive consumeristic behavior for many years. Most female students imitate the public figures as their role models. They admire at female fashion models having full of signs and meanings hence they reproducing signs and meaning for their own interests. They become addicted to buying the latest hijab fashion products regardless of neither use it or sell it. They keep uploading their own photos wearing most current fashion in Instagram. . It seems that they create an uncertainty either the use of fashionable jilbab recommended by religion or promoting them as commercial products in social media.